2020
DOI: 10.1097/cin.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Using Research Electronic Data Capture for Longitudinal Assessment Among Older Adults With Diabetes Enhances Real-Time Data Collection

Abstract: The aim of this study was to provide evidence on the application of Research Electronic Data Capture for collecting repeated data during a 7-day period among older adults. Fifty-seven adults (≥50 years) with type 2 diabetes were recruited. Participants completed one sleep diary upon awaking and one self-care diary before going to bed each day for 7 days. The diaries were administered via the Research Electronic Data Capture Web-based system and were completed via participants' own electronic devices. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For example, in a study by Sabzghabaee et al (2012), a self‐care diary was used as a resource to ‘educate the patient about their asthma and its management’ (p. 67). In a study by Zhu et al (2021), patients with T2D were provided with a self‐care diary that ‘consisted of items assessing the three main components of self‐care among patients with T2D: physical activity, eating behaviour, and medication compliance’ (p. 33). In a study by Linden et al (2018), pregnant women and young mothers with T1D were given a self‐care diary ‘for self‐reported monitoring of blood glucose, insulin doses, diet, activities and daily mood measures’ (p. 233).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study by Sabzghabaee et al (2012), a self‐care diary was used as a resource to ‘educate the patient about their asthma and its management’ (p. 67). In a study by Zhu et al (2021), patients with T2D were provided with a self‐care diary that ‘consisted of items assessing the three main components of self‐care among patients with T2D: physical activity, eating behaviour, and medication compliance’ (p. 33). In a study by Linden et al (2018), pregnant women and young mothers with T1D were given a self‐care diary ‘for self‐reported monitoring of blood glucose, insulin doses, diet, activities and daily mood measures’ (p. 233).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Zhu et al (2021), patients with T2D were provided with a self-care diary that 'consisted of items assessing the three main components of self-care among patients with T2D: physical activity, eating behaviour, and medication compliance ' (p. 33). In a study by Linden et al (2018), pregnant women and young mothers with T1D…”
Section: Self-carementioning
confidence: 99%
“…However, there are also disadvantages of this mode of data capture: costs and time involved to develop and set up the information technology (IT) infrastructure [ 8 ], increased workload for the health care professionals [ 9 , 10 ], challenges with data security [ 11 ] or digital exclusion [ 12 ]. There are also reports that electronic assessments may be more challenging for some patients [ 13 ], although other studies found that most patients prefer electronic symptom monitoring [ 14 , 15 ]. Generally, it seems that patients agree to report on their symptoms electronically but they want to talk to a person about their problems as soon as there is something of concern [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%